2018
DOI: 10.1167/18.8.11
|View full text |Cite
|
Sign up to set email alerts
|

High reward enhances perceptual learning

Abstract: Studies of perceptual learning have revealed a great deal of plasticity in adult humans. In this study, we systematically investigated the effects and mechanisms of several forms (trial-by-trial, block, and session rewards) and levels (no, low, high, subliminal) of monetary reward on the rate, magnitude, and generalizability of perceptual learning. We found that high monetary reward can greatly promote the rate and boost the magnitude of learning and enhance performance in untrained spatial frequencies and eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 88 publications
(138 reference statements)
2
54
0
Order By: Relevance
“…In essence, our results suggest that reward modulates action-specific motor resonance through the amplification of taskrelevant information (Figure 5). This is consistent with recent insights into the mechanisms of reward-based modulation which support an improvement of the signal-to-noise ratio of task-relevant characteristics (e.g., Engelmann and Pessoa, 2007;Etzel et al, 2008;Baldassi and Simoncini, 2011;Chelazzi et al, 2013;Grueschow et al, 2015;Zhang et al, 2018). Etzel and colleagues (2016) used pattern classification methods and showed that task rules were decoded more effectively on reward trials.…”
Section: Reward Sharpens the Neural Tuning Of Action Representations supporting
confidence: 84%
“…In essence, our results suggest that reward modulates action-specific motor resonance through the amplification of taskrelevant information (Figure 5). This is consistent with recent insights into the mechanisms of reward-based modulation which support an improvement of the signal-to-noise ratio of task-relevant characteristics (e.g., Engelmann and Pessoa, 2007;Etzel et al, 2008;Baldassi and Simoncini, 2011;Chelazzi et al, 2013;Grueschow et al, 2015;Zhang et al, 2018). Etzel and colleagues (2016) used pattern classification methods and showed that task rules were decoded more effectively on reward trials.…”
Section: Reward Sharpens the Neural Tuning Of Action Representations supporting
confidence: 84%
“…During the last few decades, perceptual learning has been found to improve visual performance from simple visual feature discrimination to complex object recognition, such as contrast (Yu et al, 2004;Moret et al, 2018;Zhang et al, 2018), stimulus orientation (Wang et al, 2010;Jehee et al, 2012), motion (Ball and Sekuler, 1987;Larcombe et al, 2018), stereoacuity (Ding and Levi, 2011;Xi et al, 2014), vernier acuity (Fahle and Edelman, 1993;Hung and Seitz, 2014), shape (Gilbert and Sigman, 2000;Gilbert et al, 2009), and facial recognition (Gold et al, 1999). Previous studies have shown that the improvement in learning is highly specific to the characteristics of the trained task or stimulus (Fahle and Morgan, 1996;Li et al, 2004;Huang et al, 2007) or even to the trained eye or retinal location (Karni and Sagi, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used external noise titration method to quantify the psychophysical mechanism(s) underlying age-related declines in contrast sensitivity. This method and its associated noise settings have been widely used in earlier studies [27][28][29][30][31][32][33][34] . Allard and his colleagues proposed that the property (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Observer model that incorporates nonlinear transducer function and internal multiplicative noise, i.e. perceptual template model (PTM), has been found to provide better account for visual deficits in amblyopia 27 and dyslexia 28 , system changes after perceptual learning [29][30][31] and playing video game 32 , and attention modulation 33,34 . In the current study, we attempted to re-examine the intrinsic psychophysical mechanisms underlying age-related change(s) of contrast sensitivity at a variety of spatial frequencies in a relatively large cohort of young and aging populations.…”
mentioning
confidence: 99%